Improvement of proton beam quality by an optimized dragging field generated by the ultraintense laser interactions with a complex double-layer target. (12th August 2016) - Wu, F. J.; Shan, L. Q.; Zhou, W. M.; Duan, T.; Ji, Y. L.; Wu, C. R.; Jiao, J. L.; Zhang, Z. M.; Gu, Y. Q.
Abstract: A scheme for the improvement of proton beam quality by the optimized dragging field from the interaction of ultraintense laser pulse with a complex double-layer target is proposed and demonstrated by one-dimensional particle-in-cell (Opic1D) simulations. The complex double-layer target consists of an overdense proton thin foil followed by a mixed hydrocarbon (CH) underdense plasma. Because of the existence of carbon ions, the dragging field in the mixed CH underdense plasma becomes stronger and flatter in the location of the proton beam than that in a pure hydrogen (H) underdense plasma. The optimized dragging field can keep trapping and accelerating protons in the mixed CH underdense target to high quality. Consequently, the energy spread of the proton beam in the mixed CH underdense plasma can be greatly reduced down to 2.6% and average energy of protons can reach to 9 GeV with circularly polarized lasers at intensities 2.74 × 10 22 W/cm 2 .